Puasa dalam Perspektif Al-Qur’an dan Sains - M. Azmi Ubaidillah; Edi Hermanto; M. Nahdan Syabil; M. Rapi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article aims to examine the meaning of fasting based on the Qur’an and Hadith, describe the benefits of fasting from Islamic and scientific perspectives, and analyze the challenges of practicing fasting in the modern era, particularly in the context of Qur’an memorization (tahfidz). This study employs a qualitative approach using a library research method, with primary data sources consisting of the Qur’an, the Prophet’s Hadith, classical and contemporary tafsir books, Islamic literature, and scientific studies related to health. Data were analyzed using a descriptive-analytical method. The findings indicate that fasting serves as a means of developing piety (taqwa), self-control, and spiritual purification. From an Islamic perspective, fasting cultivates patience, sincerity, and social empathy, while from a scientific perspective, fasting provides benefits for physical and mental health. Nevertheless, the practice of fasting in the digital era faces new psychological and spiritual challenges due to the rapid flow of information and technological distractions. Therefore, a comprehensive understanding of fasting is essential to ensure that the practice of fasting remains meaningful and relevant in modern life.